2021
DOI: 10.1093/mnras/stab2168
|View full text |Cite
|
Sign up to set email alerts
|

A scaling relationship for non-thermal radio emission from ordered magnetospheres: from the top of the main sequence to planets

Abstract: In this paper, we present the analysis of incoherent non-thermal radio emission from a sample of hot magnetic stars, ranging from early-B to early-A spectral type. Spanning a wide range of stellar parameters and wind properties, these stars display a commonality in their radio emission which presents new challenges to the wind scenario as originally conceived. It was thought that relativistic electrons, responsible for the radio emission, originate in current sheets formed where the wind opens the magnetic fie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
58
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 169 publications
16
58
2
Order By: Relevance
“…3). Note that the second equality recovers the empirical scaling L rad ∝ B 2 R 4 * /P 2 rot found by Leto et al (2021) and verified in Paper I.…”
Section: Split Monopole Casesupporting
confidence: 85%
See 4 more Smart Citations
“…3). Note that the second equality recovers the empirical scaling L rad ∝ B 2 R 4 * /P 2 rot found by Leto et al (2021) and verified in Paper I.…”
Section: Split Monopole Casesupporting
confidence: 85%
“…The empirical scaling relationship discovered by Leto et al (2021) and confirmed in paper I, L rad ∝ B 2 d R 4 * /P 2 rot = (Φ/Prot) 2 , is explained above as a consequence of electron acceleration via centrifugal breakout. However, Leto et al pointed out that Φ/Prot has the physical dimension of an electromotive force E (EMF), which they speculated may be suggestive of an underlying theoretical mechanism.…”
Section: Comparison With Alternative Theoretical Interpretationsmentioning
confidence: 55%
See 3 more Smart Citations